If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 4(x + 10)(x + -5) = 0 Reorder the terms: 4(10 + x)(x + -5) = 0 Reorder the terms: 4(10 + x)(-5 + x) = 0 Multiply (10 + x) * (-5 + x) 4(10(-5 + x) + x(-5 + x)) = 0 4((-5 * 10 + x * 10) + x(-5 + x)) = 0 4((-50 + 10x) + x(-5 + x)) = 0 4(-50 + 10x + (-5 * x + x * x)) = 0 4(-50 + 10x + (-5x + x2)) = 0 Combine like terms: 10x + -5x = 5x 4(-50 + 5x + x2) = 0 (-50 * 4 + 5x * 4 + x2 * 4) = 0 (-200 + 20x + 4x2) = 0 Solving -200 + 20x + 4x2 = 0 Solving for variable 'x'. Factor out the Greatest Common Factor (GCF), '4'. 4(-50 + 5x + x2) = 0 Factor a trinomial. 4((-10 + -1x)(5 + -1x)) = 0 Ignore the factor 4.Subproblem 1
Set the factor '(-10 + -1x)' equal to zero and attempt to solve: Simplifying -10 + -1x = 0 Solving -10 + -1x = 0 Move all terms containing x to the left, all other terms to the right. Add '10' to each side of the equation. -10 + 10 + -1x = 0 + 10 Combine like terms: -10 + 10 = 0 0 + -1x = 0 + 10 -1x = 0 + 10 Combine like terms: 0 + 10 = 10 -1x = 10 Divide each side by '-1'. x = -10 Simplifying x = -10Subproblem 2
Set the factor '(5 + -1x)' equal to zero and attempt to solve: Simplifying 5 + -1x = 0 Solving 5 + -1x = 0 Move all terms containing x to the left, all other terms to the right. Add '-5' to each side of the equation. 5 + -5 + -1x = 0 + -5 Combine like terms: 5 + -5 = 0 0 + -1x = 0 + -5 -1x = 0 + -5 Combine like terms: 0 + -5 = -5 -1x = -5 Divide each side by '-1'. x = 5 Simplifying x = 5Solution
x = {-10, 5}
| -2y+4(8y-7)=4+9(-9-y) | | y=-0.05x^2+0.7x | | 14x-225=5x-9 | | (x-9)(y-2)=0 | | x-9y-9=0 | | B=7a^2b | | 7x+y=1000000 | | 5x-2(6x+35)=-35 | | 2+6x=2+3x | | 2+7x=1x | | 16t^2-29+100=0 | | 448=(.08)x | | h=-16t^2-29+100 | | -0.6x+1.2=y | | 4y-12+2y+8= | | cn=400+15n | | Y=24x+.12 | | D(p)=2115-2p-p^2 | | 4-3(-1)=7 | | x^13=216 | | 5x+6-2x=-5x-x | | 3(4)+3(y)=9 | | 2n^2+17n-30= | | 3a^2+2a= | | (2t+1)(t-4)= | | x^2+11x+195=0 | | log(4)X=-2 | | x(4x-1)=3 | | 2(1-5x)=2(4x+5) | | 65+n=85-16+31 | | x+(x*.22)=745000 | | ln(x)=-2.88 |